Culturally Responsive Pedagogical Approach (CRP) Integration of Ulos Cultural Values in Christian Religious Education for Multicultural Society in Indonesia - Apriani Magdalena Sibarani (International Journal of Education and Digital Learning (IJEDL), 2025)
This research examines the integration of ulos culture in Christian religious education for multicultural communities in Indonesia, by utilizing a Culturally Responsive Pedagogy (CRP) approach. Amid the cultural and religious diversity that exists in Indonesia, Christian religious education is often trapped in a paradigm that does not consider local cultural diversity, such as the ulos culture which is very strong in the life of the Batak people. This culture has spiritual and social values that can enrich the learning of Christianity but is often marginalized in religious education curricula which are more focused on aspects of the teachings and doctrines of the religion itself. This research aims to examine how the ulos culture, which is a symbol of local Batak wisdom, can be integrated into Christian religious education through the CRP approach to create an inclusive learning space that respects cultural diversity. In this research, the author used a qualitative method with a literature study approach. The results of research on the integration of ulos culture in Christian religious education through a culturally responsive pedagogy (CRP) approach recommend a model of Christian religious education that is multidimensional, empowering, transformative, emancipatory, and promotes equality and social justice. It is hoped that this can enrich understanding, experience, and strengthen social ties, especially in a multicultural context.